Sonocatalytic Degradation of Humic Substances From Aquatic Environments Using MgO Nanoparticles - Reza Darvishi Cheshmeh Soltani (Avicenna Journal of Environmental Health Engineering, 2017)
Humic substances are considered as one of the major natural organic contaminants in water resources. Presence of such substances in the drinking water supply resources results in poor water quality and jeopardizes the consumer’s health. In the present study, sonocatalytic decomposition of the humic substances by using MgO nanoparticles was investigated under the radiation of the ultrasonic waves. Accordingly, the X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques were used to determine characteristics of the nanoparticles. Furthermore, the effects of various parameters, including the amount of nanoparticles, initial pH, initial concentration of humic substances, contact time, as well as the power and frequency of ultrasonic waves on the efficiency of the sonocatalytic decomposition of humic substances were investigated. Results of the present study showed that the efficiency of sonocatalytic decomposition of humic substances was reduced by increasing the initial pH and initial concentration of the humic substances; while, the increased amount of the nanocatalyst resulted in the increased efficiency of decomposition. Furthermore, the obtained results indicated that the MgO sonocatalytic process could decompose the humic substances with the efficiency of 78.5% under optimal conditions (pH:7, initial concentration of humic substances: 20 mg/L, concentration of nanoparticles:1 g/L, power: 100%, frequency: 37 kHz and contact time:120 min). Based on the obtained results, the sonocatalytic method using MgO can remove humic substances and other similar organic matters from the aquatic environments with a high efficiency.